2022
DOI: 10.4103/jrpp.jrpp_30_22
|View full text |Cite
|
Sign up to set email alerts
|

High-dose intravenous Vitamin C in early stages of severe acute respiratory syndrome coronavirus 2 infection: A double-blind, randomized, controlled clinical trial

Abstract: Objective: Based on previous studies in the sepsis population, Vitamin C could prevent injuries when administered in high doses and before the damage is established. This study aimed to evaluate the protective potentials of high-dose Vitamin C in the progression of coronavirus disease 2019 (COVID-19). Methods: A double-blind, placebo-controlled clinical trial was conducted. Patients with moderate-to-severe disease severity based on the World Health Organization definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Most of the randomized trials investigating the mortality outcomes with the use of vitamin C in patients with COVID-19 had some concerns of bias. In addition, other than the trial reported by Majidi et al (2021), none of the individual trials (Beigmohammadi et al 2021;Cao et al 2020;JamaliMoghadamSiahkali et al 2021;Kumar et al 2022;Kumari et al 2020;Labbani-Motlagh et al 2022;Leal-Martínez et al 2022;Tehrani et al 2022;Thomas et al 2021;Zhang et al 2021) reported significant mortality reduction with the administration of vitamin C in patients with COVID-19. In addition, variation in the dosing regimen of vitamin C used across the included trials precludes recommendation of the most appropriate method(s) for the administration of vitamin C in patients with COVID-19 to reduce their risk of mortality.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Most of the randomized trials investigating the mortality outcomes with the use of vitamin C in patients with COVID-19 had some concerns of bias. In addition, other than the trial reported by Majidi et al (2021), none of the individual trials (Beigmohammadi et al 2021;Cao et al 2020;JamaliMoghadamSiahkali et al 2021;Kumar et al 2022;Kumari et al 2020;Labbani-Motlagh et al 2022;Leal-Martínez et al 2022;Tehrani et al 2022;Thomas et al 2021;Zhang et al 2021) reported significant mortality reduction with the administration of vitamin C in patients with COVID-19. In addition, variation in the dosing regimen of vitamin C used across the included trials precludes recommendation of the most appropriate method(s) for the administration of vitamin C in patients with COVID-19 to reduce their risk of mortality.…”
Section: Resultsmentioning
confidence: 98%
“…Eight studies were excluded either due to observational study design or reported no mortality events. In total, we included eleven randomized controlled trials (Beigmohammadi et al 2021 ; Cao et al 2020 ; JamaliMoghadamSiahkali et al 2021 ; Kumar et al 2022 ; Kumari et al 2020 ; Labbani-Motlagh et al 2022 ; Leal-Martínez et al 2022 ; Majidi et al 2021 ; Tehrani et al 2022 ; Thomas et al 2021 ; Zhang et al 2021 ) in our systematic review and meta-analysis, with 445 patients randomized to receive vitamin C and 494 patients randomized to receive comparative interventions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations